Development and implementation of a DQE technique to assess image quality for digital radiology systems in the Saolta University Healthcare Group. Issue 7 (July 2016) - Donoghue, Matthew; Tuohy, Brendan; Colgan, Niall; Lavin, David; van der Putten, Wil
Abstract : Detective quantum efficiency (DQE) historically has been a commonly used metric to assess overall image quality of radiographic systems. It is defined as the ratio of the squared image signal-to-noise ratio to the number of incident X-ray photons. The DQE describes how efficiently a system translates incident X-ray photons into useful signal (relative to noise) within an image. However it is a relatively complex technique and therefore very few Medical Physicists working in Diagnostic Imaging Departments actually use the technique in practice and instead apply QA protocols based on sets of Imaging test objects whose results are prone to observer subjectivity. In 2003, the International Electrotechnical Commission (IEC) published a standard method for measurement of the DQE that also included specifications for the measurement of two associated metrics: Modulation Transfer Function (MTF) and Noise Power Spectrum (NPS). Based on this IEC standard and other published literature we developed a technique to measure MTF, NPS and DQE "in the field". In this paper we will present a summary of the methodology and some initial findings from the assessment of flat panel detector based Digital Radiography systems will be presented and explored.